Efektifitas Perbedaan Absorpsi Air Susu Ibu dan Pengganti Air Susu Ibu yang Diberikan Secara Enteral terhadap Penurunan Berat Badan Bayi Baru Lahir di RSUD Banyumas - Rahmawati, Elfira Awaliya; Saryono,; Purwandari, Haryatiningsih (Jurusan Keperawatan FIKES UNSOED, 2007)
Nutrient giving to low birth weight baby was very important for their growth and development. That nutrient could be breast milk or breast milk replacement. This research objective was to compare the effectiveness difference of breast milk, breast milk replacement or mixed of breast milk and breast milk replacement absorption at after deliveries room of Banyumas Public Hospital. Respondent of this research was 27 low birth weight baby which given breast milk, breast milk replacement or mixed of breast milk and breast milk replacement for a week. Respondent inclution criteria within this research was babies which born at 1100-2500 gram birth weight; male or female gender; low birth weight baby which pose nasogastric device without others systemic device; low birth weight baby which given mixed of breast milk and breast milk replacement. ANOVA test show that there are was not significant differences between breast milk, breast milk replacement or mixed of breast milk and breast milk replacement absorption (p > 0,05). But from average value, breast milk residue was lower than breast milk replacement or mixed of breast milk and breast milk replacement. The conclution is low birth weight baby which given breast milk is ineffective, especially at absorption and weight change than low birth weight baby which given breast milk replacement or mixed of breast milk and breast milk replacement.